Analisa Pengaruh Parameter Tekanan Terhadap Cacat Warpage Dari Produk Injection Molding Berbahan Polypropylene - Fathoni, M. Anwar (2016)
Injection molding is a plastic molding process by melting the plastic material is injected into a mold. The flaw common in injection molding products such as shrinkage, warpage, flash and incompletely fillet parts. The causes of warpage caused by the injection pressure, mold temperature, melting and holding time in the injection process (Huang and Tai, 2001). Therefore, the aim of this study was to investigate the effect of pressure on the occurrence of defects warpage of injection molding products and to determine appropriate pressure to obtain the optimal product of injection molding. The first step, a molding with a CNC milling machine and manufacturing softooling cooling system type conformal cooling channels. The method used is processing an image with a camera taking pictures using 14 pixels are processed using software solidwork warpage and height measurements using a dial indicator. This method is used for collecting data so it can be analyzed statistically and can be drawn to a conclusion. The results of the study concluded that the general increase of injection pressure makes the area the greater the warpage occurred but the warpage that occurs tends to be stable although there is optimal pressure where the pressure is the lowest warpage occurred. Optimal pressure in this study, at 11.19 kg/cm2.